The end game [compact disc, unabridged] - Coulter, Catherine; Ellison, J. T. (Coulter, Catherine. Brit in the FBI novel., 2015)
While investigating a tip from a civilian who's overheard about a possible bombing plot, the Bayway Refinery in New Jersey explodes. Nicholas and Mike race to the scene and barely escape being killed by a secondary device. Returning to the civilian's home to continue their interrogation, they discover the tipster, and the FBI team left to guard him; dead. While Nicholas calls in the assassinations, COE strikes again, this time launching a cyber-attack on several major oil companies.